Extended Hildebrand solubility approach applied to some sulphapyrimidines in some {methanol (1) + water (2)} mixtures (2023)
Extended Hildebrand solubility approach (EHSA) was applied to analyse the equilibrium solubility of sulphadiazine, sulphamerazine and sulphamethazine in some {methanol (1) + water (2)} mixtures at 298.15K. Reported experimental solubilities and some fusi